A comprehensive study of congenital unilateral absence of branch pulmonary artery associated with other congenital heart defects and ipsilateral non-unifocalizable major aorto-pulmonary collateral arteries: A single-center retrospective study - H Ravi Ramamurthy; Varsha Walavalkar; Satheesh Siddaiah; Sunita Maheshwari (Wolters Kluwer Medknow Publications, 2021)
Introduction: Congenital unilateral absence of pulmonary artery (UAPA) is a rare congenital anomaly with the complete absence of intrapericardial segment of one of the branch pulmonary arteries. Sixty percent are associated with other congenital heart defects (CHD) that often need correction. Aim To analyze the data of patients with UAPA and ipsilateral non-unifocalizable major aortopulmonary collateral arteries (MAPCAs) associated with other CHD to identify the commonly associated CHD, their management strategies and outcomes. Materials and Methods: Retrospective data of patients admitted for congenital UAPA with other CHD was compiled from hospital records from 2002 to 2015. The associated CHD were categorized as group I with the decreased pulmonary flow and group II with increased pulmonary flow to the unaffected contralateral pulmonary artery. The determinants of their management were analyzed. Results: Sixty-five patients of UAPA and ipsilateral non-unifocalizable MAPCAs associated with other CHD were identified. Group I had 41 patients and Group II had 24. The most common CHD associated with UAPA was tetralogy of Fallot (TOF) in 31 patients (47.7.2%). Fifty-three patients underwent surgery, 48 (73.8%) underwent single lung corrective surgery, 5 (7.6%) palliative surgery and 12 (18.4) received no surgery. Four operated patients died in the immediate postoperative period. The lowest Mc Goon ratio and Nakata index to undergo corrective surgery were 1.0 and 87.4 mm2/m2. A follow-up of 21 patients was done, among which 11 patients who underwent single-stage corrective surgery, all are in NYHA class II and saturating above 95%. Conclusions: Congenital UAPA is a rare anomaly and associated with a variety of CHDs, TOF being the most common. Single lung corrective surgery in patients with ipsilateral non-unifocalizable MAPCAs has good immediate and long term survival.